The Effect of Extrinsic Motivation and Gamification on Shopeefood Driver Performance in Demak Regency (International Journal of Economics and Management Research, 2026)
The development of the gig economy in Indonesia has driven an increase in the number of app-based work partners, including ShopeeFood drivers in Demak Regency. However, previous studies have shown inconsistent results regarding the effect of extrinsic motivation and gamification on driver performance, particularly in mid-sized cities with lower order volumes. This study aims to analyze the effect of extrinsic motivation and gamification on the performance of ShopeeFood drivers in Demak Regency. The approach used was quantitative with a saturated sampling technique (census sampling) of 105 active drivers as of December 12, 2025. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that extrinsic motivation had a positive and significant effect on performance (β = 0.299; sig. 0.000), as did gamification (β = 0.266; sig. 0.000). Income, incentives, job security, and working conditions, as well as gamification systems such as points, rewards, leaderboards, and levels, have been shown to increase driver engagement and performance. It was concluded that both variables effectively improved performance, so companies need to design extrinsic motivation and gamification systems that are realistic and adaptive to the characteristics of medium-sized cities.